Gestão de energia no saneamento : estado atual e perspectivas para melhorias no setor - Queiroz, Bianca Silva (2017)
The management of electricity in sanitation companies has become a challenge for companies in the sector. The motor-pump assemblies and all the processes that treat and carry the treated water to the population and that collect the sanitary sewage destined to the appropriate treatment have demanded the increase of the use of the electric energy. In this way, electricity has become the second largest item for water and sewage companies, losing only to the human resources payroll. In view of this problem, the objective of this work was to describe the energy management in Brazilian sanitation companies and to verify the greatest difficulties for an effective energy management based on the requirements of ABNT NBR ISO 50001. For realization of this work, capixabas sanitation companies were interviewed and an on-line questionnaire was sent to sanitation companies located in Brazil. The analysis of the interview responses was performed using the Discourse Analysis method and the analysis of the questionnaire responses were analyzed through descriptive statistics using the Microsoft Excel and SPSS Statistics softwares. By means of the obtained results, it can be concluded that the energy management in the sanitation companies is carried out in a differentiated way each with its necessity. The sanitation companies are looking for ways that tend to be successful for an effective energy management alternative to that of ABNT NBR ISO 50001, and only 7.5% of the companies interviewed have this certification.